Clinical prognostication of out-of-hospital cardiac arrest: insight from a prospective observational study using the shockable, witnessed, age and pH score - K. J., Jasmine; Rajeev, P. C.; V. Abraham, Siju; Varghese, Salish (International Journal of Research in Medical Sciences, 2023)
Background: Cardiac arrest remains a leading cause of mortality and morbidity worldwide. Though there are many prognostic tools, the importance of predicting prognosis of out of hospital cardiac arrest in the emergency department (ED) using SWAP (Shockable, witnessed, age and pH) score has not been studied extensively. Methods: We conducted a hospital-based prospective observational study in Kerala, India, focusing on patients who arrived at the ED after experiencing out-of-hospital cardiac arrest (OHCA). For patients who met the inclusion criteria, (all patients who came to ED with OHCA with age more than 18 years) we calculated the SWAP score using historical information and venous blood gas sample analysis. Patients who achieved return of spontaneous circulation (ROSC) were closely monitored, and post-cardiac arrest care was initiated. Patients who achieved sustained ROSC were admitted, and at time of discharge, follow-up was conducted using cerebral performance category (CPC) score. Results: The SWAP score was computed for patients who experienced OHCA. The analysis revealed that patients with favorable outcomes (CPC 1 and 2) had an average SWAP score of 1, while patients with unfavorable outcomes (CPC 3, 4, 5) had an average SWAP score of 1.55. Among the total of 116 patients, 7 individuals (6.03%) survived with positive neurological outcomes (CPC 1 and 2), while 109 patients (93.96%) experienced poor neurological outcomes (CPC 3, 4, 5, and mortality). Conclusions: Patients who had a high SWAP score had a reduced likelihood of survival and sustained ROSC. Conversely, patients with a SWAP score below 2 had a higher probability of experiencing a ROSC and surviving.